The vernacular: three essays on an ambivalent concept and its uses in South Asia - Harder, Hans; Zaidi, Nishat; Tschacher, Torsten (Routledge, 2024)
"This book examines the validity of the notion of the 'vernacular' and the position of the so-called 'vernaculars' in colonial and postcolonial settings. It addresses recent formulations and debates regarding the status of regional languages of South Asia in relation to English. The authors explore the range of meanings the term has assumed and trace a history of contestation since the colonial age. They contend that though the 'vernacular' in South Asia has, since the 19th century, often operated as a hegemonic category relegating the languages thus designated to an inferior status, those languages (and other cultural formations labeled as 'vernacular') have also received empowering impulses and vested with qualities like groundedness and strength. The book highlights the need for a critical discussion of the notion of the 'vernacular' in the context of the ongoing rise of Anglophonia in South Asia as a whole, and post-liberalization India in particular. The volume will be of great interest to scholars and researchers of literary and culture studies, history, postcolonial studies and South Asian studies"--